[AR] al-Mafahim al-Tahwiliyyah li Wilhelm Dilthey fi Ughniyyah “Ya Lal Wathan”: The Hermeneutic Concept of Wilhelm Dilthey in the Song “Ya Lal Wathan” (Afaq Lughawiyyah, 2024)
There were previous studies about the song Ya Lal Wathan with many perspectives. Now the study about it will be done with literature perspective, especially hermeneutic. This study aims to reveal the three concepts of hermeneutic of Wilhelm Dilthey in the son Ya Lal Wathan. This belongs to descriptive qualitative study that uses library study. The primary data in this study is the song Ya Lal Wathan that was composed by KH. Abdul Wahab Hasbullah. After doing this study, the researcher finds some results as follows. In the first concept of hermeneutic which is called the concept of experience (erlebnis), there is a deep relation between the song author biography and the history of song creation. The song author is a person who has an important role in the struggle for Indonesian independence. So, his enthusiasm and invitation for loving the homeland and his encouragement to preserve the homeland are depicted in the song he composed. In the second concept, which is called the concept of expression (ausdruck), there are beautiful stylistic phrases that express what the author intended through the verses of the song. They are the style of ijaz, repetition, and the use of the hidden and prominent pronoun I. In the third concept, which is called the concept of understanding (verstehen), there is the author’s invitation to love the homeland for all the people of the homeland and his encouragement to protect the homeland from all threats.